2014
DOI: 10.3892/or.2014.2975
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fatty acid binding protein 4 is involved in the cell growth of oral squamous cell carcinoma

Abstract: Abstract. Fatty acid binding proteins (FABPs) are a family of small and highly conserved lipid chaperone molecules with highly varied functions. Among them, fatty acid binding protein 4 (FABP4, also known as aP2) is highly expressed by adipocytes, macrophages and dendritic cells. Although the role of FABP4 in cancer is still unclear, it has been reported to be highly expressed by human tumors such as ovarian and bladder cancers. In the present study, we investigated the expression and role of FABP4 in oral squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…Several studies have demonstrated the association between FABP4 expression and poor prognosis in several tumors [38-40], which were consistent with our current findings. However, the role of FABP3 in tumor is controversial: FABP3 can act as either a tumor suppressor or an oncogene depending on tumor types.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have demonstrated the association between FABP4 expression and poor prognosis in several tumors [38-40], which were consistent with our current findings. However, the role of FABP3 in tumor is controversial: FABP3 can act as either a tumor suppressor or an oncogene depending on tumor types.…”
Section: Discussionsupporting
confidence: 93%
“…It functions in both glucose and lipid metabolism [29, 30], and is involved in signal transduction [31], as well as in cell proliferation and apoptotic processes [32]. Its involvement in tumorigenesis has been investigated in bladder cancer [12], breast cancer [33, 34], ovarian cancer [35, 36], and oral squamous cell cancer [37]. However, there have been few studies of FABPs in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 Other investigators have described potential roles for FABP4 in endothelial cell growth and blood vessel branching, 108113 and FABP4 has also been implicated in cancer cell growth and metastasis. 114116 The mechanisms that underly these effects are not fully understood and indeed might be pleiotropic; for example, whether the protection from asthma in Fabp4 − / − mice 40 is due to changes in immune responses, alterations in bronchoepithelial cells, other stromal cells or both, is unclear. Finally, conditions of ectopic lipid accumulation in tissues, especially in the presence of inflammatory and stress responses, might produce a permissive milieu that activates aberrant FABP expression in cells such as hepatocytes, or trigger expression from resident immune cells such as Kupffer cells.…”
Section: Other Intracellular Fabp Functionsmentioning
confidence: 99%
“…However, it has been shown that FAS is overexpressed in numerous human cancers, including bladder cancer, and its expression level is positively correlated with tumor progression [67]. Similar to FAS, fatty acid binding proteins (FABPs) are involved in lipid metabolism and facilitate the transfer of lipids, including lipid droplets for storage, across various cellular membranes and compartments [6870]. Adipocyte-type FABP (A-FABP), also known as adipocyte protein 2 (aP2) and fatty acid binding protein 4 (FABP4), binds to long chain fatty acids and PPAR γ agonists [69].…”
Section: An Independent Microenvironment Through Pparγmentioning
confidence: 99%